Future use of new imaging technologies in developing countries : report of a WHO scientific group, meeting held in Geneva from 24 September to 1 October 1984 - WHO Scientific Group on the Future Use of New Imaging Technologies in Developing Countries; World Health Organization (Geneva : World Health Organization, 1985)
An expert guide for developing countries contemplating the introduction and use of diagnostic ultrasound or computed tomography. Sensitive to the needs and priorities of developing countries, the book helps planners assess these new technologies in terms of technical requirements, initial costs, ongoing running expenses, demands on manpower resources, and the advantages and disadvantages for the patient. Incorporating well over 300 references, the book also discusses the specific clinical applications where use of ultrasound or computed tomography can bring a substantial improvement in diagnostic results or safety and comfort for the patient
1. General Introduction -- 2. Ultrasound -- 3. Computed tomography -- 4. Clinical indications -- 5. Summary of recommendations -- Acknowledgements -- References
Keywords: Ultrasonography; Tomography, X-Ray Computed; Developing Countries; Pharmacology, Toxicology and Clinical Technology